Possibility of earlyseason culture of water yam (Dioscorea alata L.) in Yaku island - Onjo, M.; Shiwachi, H.; Hayashi, M. (2003)
Early-season culture of water yam was required in Yaku Island, because of the long growing period, the concentrating work at the harvesting time, the lack of storehouse and so on. Thus we tried to search the early-maturing strains and use a plant growth regulator that promote the tuber enlargement. Then we found out the extremely early maturing strains introduced from high altitude area in the Kingdom of Nepal. On the other hand, foliar applications of gibberellins promoted the tuber enlargement. These results suggest the possibility of early season culture of water yam. Further research would be required to use the new strains and the plant growth regulator.